2021
DOI: 10.1186/s13041-021-00848-w
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal traffic and glutamate synapse activity are increased in VPS35 D620N mutant knock-in mouse neurons, and resistant to LRRK2 kinase inhibition

Abstract: Vacuolar protein sorting 35 (VPS35) regulates neurotransmitter receptor recycling from endosomes. A missense mutation (D620N) in VPS35 leads to autosomal-dominant, late-onset Parkinson’s disease. Here, we study the basic neurobiology of VPS35 and Parkinson’s disease mutation effects in the D620N knock-in mouse and the effect of leucine-rich repeat kinase 2 (LRRK2) inhibition on synaptic phenotypes. The study was conducted using a VPS35 D620N knock-in mouse that expresses VPS35 at endogenous levels. Protein lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 92 publications
5
11
0
Order By: Relevance
“…However, we can recapitulate two robust findings associated with the VPS35 (D620N) mutation i.e. diminished interaction between retromer and the WASH complex and activation of LRRK2 [19, 20, 23]. This second facet is the main focus of our study, as it reflects a direct connection between two pieces of the Parkinson’s Disease jigsaw.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, we can recapitulate two robust findings associated with the VPS35 (D620N) mutation i.e. diminished interaction between retromer and the WASH complex and activation of LRRK2 [19, 20, 23]. This second facet is the main focus of our study, as it reflects a direct connection between two pieces of the Parkinson’s Disease jigsaw.…”
Section: Discussionsupporting
confidence: 67%
“…Many suggestions have been made for the patho-physiological role of VPS35 (D620N) that use known retromer-dependent pathways as their inspiration. In addition, a persuasive link between VPS35 and LRRK2 has been established, in that VPS35 (D620N) results in hyperactivation of LRRK2 [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, human induced pluripotent stem cell (iPSC)-derived dopaminergic neurons harbouring the D620N mutation were also observed to have an increase in GluR1 cluster intensity. Supporting these findings, a recent study by Kadgein et al [45] observed GluR1 association with VPS35 in neurons derived from a D620N VPS35 knockin mouse model. While previous studies have used overexpression of VPS35 variants, D620N VPS35 knockin mice provide a more physiologically relevant model, expressing VPS35 at endogenous levels.…”
Section: Neurotransmission Defectssupporting
confidence: 56%
“…Notably, VPS35 mRNA is detected in the mammalian brain where it is highly expressed in frontal cortex, hippocampus, striatum and cerebellum, and shows highest expression in neurons and oligodendrocytes [43]. Moreover, VPS35 is required for various cellular mechanisms, as evidenced by defects in WASH complex binding, AMPA receptor sorting, the autophagy-lysosomal pathway, and mitochondrial dynamics and activity induced by the PDlinked D620N mutation [44][45][46][47]. Interestingly, while the D620N mutation does not disrupt the interaction of VPS35 with other subunits of the retromer complex, there is some discordance within the literature surrounding the mechanism of VPS35-dependent neurodegeneration.…”
Section: Vps35 and The Retromermentioning
confidence: 99%
“…Although limited evidence is available, several studies claim that the disorder in retromer function by PD-related VPS35 mutations may affect synaptic function (Figure 3). In mouse primary cortical neurons, the presence of D620N VPS35 was less frequently present in dendritic spines than WT VPS35, and D620N VPS35 tended to form clusters with FAM21 in EEs (Munsie et al, 2015;Kadgien et al, 2021). In the synaptic nerve terminal, VPS35 participates in the cell surface recycling of GluA1, dopamine D1 receptor (D1R), and dopamine transporter (DAT), and thus, D620N VPS35 might increase the surface expression of these receptors, thereby producing chronic stress in neuronal circuits (Munsie et al, 2015;Wu et al, 2017;Kadgien et al, 2021).…”
Section: Molecular and Cellular Mechanisms Underlying Familial Parkin...mentioning
confidence: 99%